Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Pada Produk Sepatu Lokal Merek Aerostreet (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Prodi Manajemen Universitas Bhayangkara Jakarta Raya) - Chandra, Steve Febrian; Untari, Dhian Tyas; Rohaeni, Heni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Local brands are now able to compete with imported products thanks to creative designs, competitive quality, and adaptive digital marketing strategies. This phenomenon is supported by large-scale promotions promoting love for local products. This study aims to determine the partial and simultaneous effects of product quality, price, and promotion on purchasing decisions for Aerostreet brand local shoes. This study employs a quantitative approach using a survey method and data collection techniques via questionnaires. The sampling technique used is saturation sampling, with a population of 33 respondents who are students of the Faculty of Economics and Business, Management Program, at the University of Bhayangkara Jakarta Raya, from the 2021 and 2022 cohorts, who have previously purchased Aerostreet footwear products. Data processing and hypothesis testing were conducted using SPSS software version 25. The results of the study indicate that product quality, price, and promotion partially have a positive and significant influence on purchasing decisions. Simultaneously, all three variables also have a positive and significant influence on purchasing decisions for local Aerostreet brand shoes.